2014
DOI: 10.1016/j.jtcvs.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Complex aortic surgery in a regional center in the United Kingdom. Should the United Kingdom now adopt a United States–style supercenter model?

Abstract: Our outcomes are comparable with other regional centers worldwide; however, they are not as good as those reported from the aortic supercenters. There should be continued impetus regarding the establishment of thoracic aortic surgery guidelines and specialist aortic centers in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
5
1
1
Order By: Relevance
“…Deep hypothermic circulatory arrest to a rectal temperature of 17 C without specific cerebral perfusion protocol was also used. Although Ariyaratnam and colleagues, 1 did not provide any data on circulatory arrest length, and arch replacement occurred in just 2.9% of the cases, current data suggest that antegrade cerebral perfusion and mild-to-moderate systemic hypothermic circulatory arrest can be safely applied to complex thoracic aortic surgery, ameliorating postoperative ouctomes. 5 So although Ariyaratnam and colleagues 1 set out to demonstrate the need to adopt a US-style supercenter model for TAD, it appears that their analysis understimates the effects of an optimized patient management on the hospitalization outcome, especially in regional centers.…”
Section: Thoracic Aortic Surgery In Europe: Does Volume Mean Necessarily Quality?contrasting
confidence: 54%
See 3 more Smart Citations
“…Deep hypothermic circulatory arrest to a rectal temperature of 17 C without specific cerebral perfusion protocol was also used. Although Ariyaratnam and colleagues, 1 did not provide any data on circulatory arrest length, and arch replacement occurred in just 2.9% of the cases, current data suggest that antegrade cerebral perfusion and mild-to-moderate systemic hypothermic circulatory arrest can be safely applied to complex thoracic aortic surgery, ameliorating postoperative ouctomes. 5 So although Ariyaratnam and colleagues 1 set out to demonstrate the need to adopt a US-style supercenter model for TAD, it appears that their analysis understimates the effects of an optimized patient management on the hospitalization outcome, especially in regional centers.…”
Section: Thoracic Aortic Surgery In Europe: Does Volume Mean Necessarily Quality?contrasting
confidence: 54%
“…The use of an intra-aortic balloon pump in patients with TAD, fragile tissues, and peripheral vascular disease could partially explain the hospitalization outcomes presented in the article of Ariyaratnam and colleagues. 1 As a matter of fact, peripheral vascular disease and hypertension were independent predictors for in-hospital mortality (odds ratios of 14.428 and 9.325, respectively), especially in the dissection group, possibly reflecting the negative effects of intra-aortic balloon pumps on these patients. In addition, Ariyaratnam and colleagues 1 adopted central cannulation or femoral artery cannulation for all patients, including those affected by type A dissection.…”
Section: Thoracic Aortic Surgery In Europe: Does Volume Mean Necessarily Quality?mentioning
confidence: 95%
See 2 more Smart Citations
“…This decision making is partly based on the estimated risk of dissection in patients with BAV to be 8 times higher than that in the general population [27]. Our series, for elective and urgent cases, is the largest reported in the United Kingdom to date, with favorable results compared with series reporting mortalities of 7% to 16% and others reporting elective and urgent mortality of 3.5% to 9% [10,[28][29][30]. Stamou and colleagues [31] analyzed the Society of Thoracic Surgeons database and reported that the median number of procedures per year was 2 per center, with an operative mortality of 4.2%.…”
Section: Commentmentioning
confidence: 99%